2020
DOI: 10.15673/fst.v14i3.1792
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters of Semi-Finished Sponge Cake Enriched With Pumpkin by-Products

Abstract: Nowadays, there is growing demand for flour-based products that only contain natural ingredients and are highly nutritional. This tendency promotes further research to find new raw materials for their production. Using by-products of pumpkin processing is a promising way to solve this problem due to their chemical content. In this research, the physicochemical and sensory properties of sponge cake enriched with pumpkin seed powder in two different quantities (5% and 10%) have been studied. Sensory evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Numerous works have shown that inexpensive raw materials can be available as a source of functional food ingredients for confectionery products. Such is non-traditional fruit and vegetable raw materials or waste [5,6], secondary or non-traditional resources of flour-grinding production [7][8][9], products of extrusion of grain crops [10], traditional and new types of dairy, fatty products [11,12], medicinal plants [13 ], which are carriers of essential and valuable substances.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have shown that inexpensive raw materials can be available as a source of functional food ingredients for confectionery products. Such is non-traditional fruit and vegetable raw materials or waste [5,6], secondary or non-traditional resources of flour-grinding production [7][8][9], products of extrusion of grain crops [10], traditional and new types of dairy, fatty products [11,12], medicinal plants [13 ], which are carriers of essential and valuable substances.…”
Section: Introductionmentioning
confidence: 99%